Bovine leukosis virus and antibodies against bovine herpesvirus type-1 and bovine viral diarrhea virus and in buffaloes of the State of Pará, Brazil - Viana, Rinaldo Batista; Del Fava, Claudia; Monteiro, Bruno Moura; de Barros Moura, Ana Carolina; dos Santos Albuquerque, Rodrigo [UNESP]; da Cruz Cardoso, Elyzabeth; de Araújo, Cláudio Vieira; Pituco, Edviges Maristela (Universidade Federal do Rio Grande do Sul, 2018)
Background: Viral diseases affecting reproduction cause economic losses in cattle, as reproductive failure interrupts the production cycle, thus reducing herd productivity. Buffaloes are susceptible to most of the diseases that affect cattle. Some of the viral diseases of reproductive importance are infectious bovine rhinotracheitis (IBR), bovine viral diarrhea (BVD), and bovine leukosis (BL). The objective of this study was to determine the seroprevalence of IBR virus (bovine herpes virus-1, BoHV-1), BVD virus (BVDV), and BL virus (BLV) in female buffaloes living in wetland areas or plains in the state of Pará, as well as the seroprevalence of BoHV-1, BVDV, and BLV in females of different age groups. Materials, Methods & Results: It were used 225 crossbred buffaloes from 4 buffalo exclusive farms. The buffaloes reared on farms A (n = 50) and B (n = 89) were kept in wetland areas on Marajó Island (n = 139), Pará. On farms C (n = 30) and D (n = 56) buffaloes were kept in plains (n = 86) in a northeastern mesoregion of Para. Animals were categorized into age groups: I: 0-3 years (n = 34), II: 3-6 years (n = 58), III: 7-9 years (n = 55), and IV: over 9 years (n = 78). Blood samples were collected and sera were sent for processing at the Bovine Virus Laboratory, Biological Institute of São Paulo, Brazil. The presence of IBRV and BVDV was determined by neutralization and BLV antibodies by immunodiffusion in agar gel. Statistical analysis was performed using the x2 test at a significance level of 5%. Among the seroprevalences of IBRV, BVDV and BLV antibodies, the difference in prevalence for BVD [P < 0.01] was observed between wetland areas and plains of Para, varying from 12.4% to 96.0% and 0.0% to 13.3%, respectively. While levels of IBRV remained high on farms A (79.6%), B (86.5%), C (83.3%) and D (89.1%) [P = 0.60] and BLV was negative in all the animals. BVDV was similar for all the age groups [P = 0.60], while IBRV was more prevalent in animals over 6 years of age with group I: (76.5%), II (74.5%), III (92.3%) and IV (91.3%) [P = 0.01]. It was not possible verify the influence of age in prevalence for BL. Discussion: The prevalence obtained for the BoHV-1 on farms was high, with little variation between 79.6% and 89.1%. The high prevalence of BoHV-1 suggests the free circulation of the virus in the state of Para. Notably, the animals in this study had not been vaccinated, so the determined viral antibody titers were independent of vaccination. BVDV results showed high variation between 0.0% and 96.0%. The highest prevalence in wetland areas may be related to the breeding environment, because of a possible horizontal contamination. The lack of BLV antibodies prevalence can be attributed to the fact that all the evaluated animals were kept in an extensive breeding system where they had little direct contact. The prevalence of IBR was higher in the older animals. Variation in prevalence with age was not observed for BVD. It was concluded that the prevalence for IBR and BVD were high indicating that the etiological agents are circulating in Para, with IBR having a higher prevalence in older animals. Breeding buffalo in wetland areas may favor horizontal transmission of BVDV because facilitate contact of healthy animals with water contaminated by virus carriers animal secretion and the absence of seropositive animals at the BLV does not necessarily indicate that buffaloes are resistant to the virus.
Ocorrência do vírus da leucose enzoótica dos bovinos (BLV) e de anticorpos contra herpesvírus bovino tipo-1 (BoHV-1) e vírus da diarreia viral bovina (BVDV) em búfalos no Estado do Pará
Keywords: Buffalo; BVD; IBR; Leukosis; Viral diseases